Partial Eclogitization of the Ambolten Gabbro-norite, North-east Greenland Caledonides - Gilotti, J. A.; Elvevold, S. (Bulletin Suisse de Mineralogie et Petrographie, 1998)
Partially eclogitized igneous bodies composed of gabbro, leucogabbro, anorthosite and cross-cutting diabase dikes are well represented in the North-East Greenland Eclogite Province. A 200 x 100 meter intrusive body on Ambolten Island (78?? 20' N, 19?? 15' W) records a prograde transition from gabbro-norite to eclogite facies coronitic metagabro-norite surrounded by hydrated margins of undeformed to strongly foliated amphibolite. Igneous plagioclase + olivine + enstatite + augite + oxides convert to eclogite facies assemblages consisting of garnet, omphacite, diopside, enstatite, kyanite, zoisite, rutile and pargasitic amphibole through several coronitic reactions. Relict cumulus plagioclase laths are replaced by an outer corona of garnet, an inner corona of omphacite and an internal region of sodic plagioclase, garnet, kyanite, omphacite and zoisite. Olivine and intercumulus pyroxene are partly replaced by metamorphic pyroxenes and amphibole. The corona structures, zoning patterns, diversity of mineral compositions in a single thin section, and preservation of metastable asemblages are characteristic of diffusion-controlled metamorphism. The most extreme disequilibrium is found in static amphibolites, where igneous pyroxenes, plagioclase domains with eclogite facies, assemblages, and matrix amphibole coexist. Complete eclogitization was not attained at Ambolten due to a lack of fluids needed to drive diffusion during prograde and retrograde metamorphism. The P-T conditions of the high-pressure metamorphism are estimated at ??? 750??C and > 18 kbar. Well-equilibrated, foliated amphibolites from the margin of the gabbro-norite supports our contention that the entire North-East Greenland Eclogite Province experienced Caledonian high-pressure metamorphism, even though no eclogite facies assemblages have been found in the quartzofeldspathic host gneisses to date.
Keywords: anorthosite; cross-cutting diabase dikes; eclogitized igneous bodies; gabbro; leucogabbro; North-East Greenland